Transmission of composite polymerization contraction force through a flowable composite and a resin-modified glass ionomer cement - Juan Carlos Castañeda-Espinosa; Rosana Aparecida Pereira; Ana Paula Cavalcanti; Rafael Francisco Lia Mondelli (University of São Paulo, 2007)
The purpose of this study was to evaluate the individual contraction force during polymerization of a composite resin (Z-250), a flowable composite (Filtek Flow, FF) and a resin-modified glass ionomer cement (Vitrebond, VB), and the transmission of Z-250 composite resin polymerization contraction force through different thicknesses of FF and VB. The experiment setup consisted of two identical parallel steel plates connected to a universal testing machine. One was fixed to a transversal base and the other to the equipment's cross head. The evaluated materials were inserted into a 1-mm space between the steel plates or between the inferior steel plate and a previously polymerized layer of an intermediate material (either FF or VB) adhered to the upper steel plate. The composite resin was light-cured with a halogen lamp with light intensity of 500 mW/cm² for 60 s. A force/time graph was obtained for each sample for up to 120 s. Seven groups of 10 specimens each were evaluated: G1: Z-250; G2: FF; G3: VB; G4: Z-250 through a 0.5-mm layer of FF; G5: Z-250 through a 1-mm layer of FF; G6: Z-250 through a 0.5-mm of VB; G7: Z-250 through a 1-mm layer of VB. They were averaged and compared using one-way ANOVA and Tukey test at a = 0.05. The obtained contraction forces were: G1: 6.3N + 0.2N; G2: 9.8 + 0.2N; G3: 1.8 + 0.2N; G4: 6.8N + 0.2N; G5: 6.9N + 0.3N; G6: 4.0N + 0.4N and G7: 2.8N + 0.4N. The use of VB as an intermediate layer promoted a significant decrease in polymerization contraction force values of the restorative system, regardless of material thickness. The use of FF as an intermediate layer promoted an increase in polymerization contraction force values with both material thicknesses.